Evaluation of Yield Attributing Trait of Spring Wheat Genotypes Under Normal and Late Sowing Condition - Jaisi, Sushil; Thapa, Asha; Poudel, Mukti Ram (Talenta Publisher, 2022)
Wheat (Triticum aestivum) is the third most important cereal crop in Nepal after rice and maize. The research is carried out during the winter season in agronomic field of the Institute of Agriculture and Animal Science (IAAS), Bhairahawa, Nepal. Sowing is carried out 28th November 2020 and 24th December 2020 on alpha lattice design with two replication of twenty wheat genotype under normal and late sowing respectively. In the late sowing condition, all genotype's performance is reduced as compared to normal sowing. Under late sown condition, high temperatures reduced the days to booting (15.64%), days to heading (14.97%), days to maturity (14.16%), chlorophyll content (15.99%), plant height (8.59%), spike length (7.03%), number of spikelet per spike (9.21%), number of grain per spike (10.6%), spike weight (15.32%), effective tiller/m2 (9.92%), thousand kernel weight (10.3%) and grain yield (22.5%). NL 1420 presented higher 4118 kg/ha and 3310.5 kg/ha yield respectively and BL 4407 presented early maturity 119.2 DAS and 100.6 DAS respectively in normal sowing and late sowing condition. In a combined environment, maximum grain yield is recorded in NL1420. The result suggested that the tolerant line against the late sowing condition can be used as genetic resource for crop improvement and promote for grain yield.